Review of Non-natives writing for Anglo-American journals: Challenges and urgent needs; Author: Katarzyna Hryniuk; Publisher: Warsaw University Press, 2019; ISBN: 978-83-235-3677-2; Pages: 172 - Gabryś-Barker, Danuta (Studies in Second Language Learning and Teaching, 2020)
I was looking forward to a publication of a scholarly text on academic writing and on the publishing process, which both have such an important impact on the professional experience of Polish scholars. The book by Katarzyna Hryniuk, entitled Non-Natives Writing for Anglo-American Journals: Challenges and Urgent Needs, fulfils this need. The monograph, 172 pages in length, includes an introductory section, six chapters, an appendix, an extensive list of references, topic and author indexes, and a short summary in Polish. It offers a fairly complete picture of issues in academic publication with a unique focus on Poland.